Cationic state Pt single-site catalyst as well as preparation method and application thereof
Through Ce doped cationic Pt unit-point catalyst, the problem of existing Pt-based catalysts being easily deactivated in the direct dehydrogenation reaction of propane is solved, and an efficient and stable propane dehydrogenation reaction is achieved, which is suitable for large-scale production of propylene.
Patent Information
- Application Number
- CN202411597325.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The existing Pt-based catalysts are prone to inactivation due to carbon deposits and sintering in the direct dehydrogenation reaction of propane, and are costly, making it difficult to meet the needs of efficiently preparing propylene.
A cationic Pt unit-point catalyst is used for the SiO2 support, which is supported by a ternary metal component composed of Pt, Ce and M (M=Fe, Zn, Ga, In) and is dissolved, impregnated, dried and calcined by ultrasonic dissolution, impregnation, drying and calcination. Preparation through the same steps has been achieved to achieve efficient propane dehydrogenation reaction.
The catalyst showed excellent catalytic activity and high temperature stability under harsh reaction conditions, with propane conversion of more than 65%, propylene selectivity of more than 92%, and the preparation process is simple and the cost is low.
Smart Images

Figure CN119425683A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation, and in particular relates to a cationic Pt single-site catalyst and a preparation method thereof, and application of the catalyst in direct dehydrogenation of propane to produce propylene. Background Art
[0002] Propylene is an important raw material for chemical production. Its downstream products include polypropylene, isopropanol, propylene oxide, acrylonitrile, etc., which are involved in various aspects of daily life such as clothing manufacturing, medical equipment, mechanical parts and food packaging. It can be said that it has a wide range of uses and a huge amount of use. In the production process of propylene, there are mainly fluid catalytic cracking (FCC), steam cracking of naphtha and light diesel (SCC), olefin disproportionation, methanol / coal to olefins (MTO / CTO) and other process technologies. However, most processes have high costs, high energy consumption, low propylene yields, and even recover propylene as a by-product. Its output and quality cannot meet the growing high-quality demand. In contrast, propane dehydrogenation (PDH) is a propylene-specific process that has attracted much attention for its highest propylene selectivity and lower cost.
[0003] In the PDH reaction, Pt-based catalysts have the advantages of good CH bond activation ability and environmental friendliness, and are currently the most widely used industrial catalysts. However, industrially used PtSn catalysts are easily deactivated due to carbon deposition and sintering, and require frequent regeneration with chlorine, which not only increases production and time costs, but also causes certain pollution to the environment. Therefore, researchers are eager to adopt more effective strategies to inhibit carbon deposition and sintering and extend their service life. Usually, the introduction of additives can overcome these shortcomings to a certain extent. Therefore, the use of additive doping to design highly active and highly stable Pt-based catalysts is the most efficient and simple strategy.
[0004] Xinwen Guo's group (ACS Catalysis, 2022, 12, 6559-6569) et al. synthesized a supported Pt1Fe7 / S-1 catalyst by impregnation and introduced CO into the PDH reaction. 2 To inhibit the metal Fe 0 species to avoid metallic Fe 0 The generation of species induces carbon deposition, which in turn leads to rapid deactivation of the catalyst. Although this method has achieved a certain promoting effect, it still cannot maintain the structural stability of the catalytic active sites.
[0005] The patent (CN 113042098A) discloses a PtIn catalyst wrapped with an MFI molecular sieve, which is a Pt(NH 3 ) 4 (NO 3 )2 The aqueous solution and the TPAOH solution are mixed to obtain a first mixed solution; TEOS and the first mixed solution are mixed to obtain a second mixed solution; In(NO 3 ) 3 ·xH 2 O solution is mixed with the second mixed solution to obtain a third mixed solution; the third mixed solution is subjected to hydrothermal treatment to obtain a treated product; the treated product is calcined to obtain a PtIn@MFI catalyst. However, the hydrothermal preparation process is relatively complicated, the catalyst cost is relatively high, and it is not conducive to large-scale expansion.
[0006] The above studies show that the bimetallic PtM (M = Fe, Zn, Ga, In) catalyst synthesized by conventional strategies is not only easy to deactivate, but also has disadvantages such as low Pt utilization efficiency. Therefore, it is of great significance to adopt a simpler and more efficient synthesis strategy to prepare Pt single-site ternary catalysts with stable performance to improve the catalytic conversion efficiency of propane molecules. Summary of the invention
[0007] The purpose of the present invention is to provide a cationic Pt single-site catalyst formed by Ce doping, a preparation method thereof, and an application thereof in a propane dehydrogenation reaction. The preparation process is simple, which is conducive to maximizing the utilization efficiency of precious metal atoms in the Pt-based catalyst, and shows excellent catalytic activity and high temperature stability in the process of propane dehydrogenation to propylene under harsh reaction conditions, providing a new way for the dehydrogenation of alkanes to high value-added olefins.
[0008] To achieve the above object, the present invention adopts the following technical solution: A cationic Pt single-site catalyst based on SiO 2 As a carrier, a ternary metal component consisting of Pt, Ce and M is loaded on its surface; wherein M is any one of Fe, Zn, Ga and In, and Pt is in a unit-point cationic state in the ternary metal component.
[0009] Furthermore, based on the sum of the molar percentages being 100%, in the ternary metal component, the content of Pt is 5.6% to 49.3%, the content of Ce is 29.2% to 84.8%, and the content of M is 8.7% to 50.7%.
[0010] The preparation method of the cationic Pt single-site catalyst comprises the following steps: (1) dissolving the nitrate precursors of Pt, Ce and M in deionized water by ultrasonication at room temperature to prepare a uniformly mixed transparent metal salt precursor aqueous solution; (2) The metal salt precursor aqueous solution prepared in step (1) is loaded onto SiO by impregnation method. 2On the carrier, a white solid sample was obtained; (3) The white solid sample obtained in step (2) is carefully ground and then calcined in a muffle furnace to obtain the catalyst.
[0011] Furthermore, the ultrasonication time in step (1) is 2 to 60 min.
[0012] Furthermore, the total metal ion concentration of the metal salt precursor aqueous solution obtained in step (1) is 0.3-1.3M.
[0013] Furthermore, the volume of the aqueous solution of the metal salt precursor used in step (2) is 0.5 to 3 times the pore volume of the support.
[0014] Furthermore, in step (2), the metal salt precursor aqueous solution is slowly added to SiO 2 The carrier was sealed and allowed to stand at room temperature for 1-2 h, then transferred to a static oven and dried at 50-100 °C for 8-24 h.
[0015] Furthermore, the calcination in step (3) is carried out in static air at 400-600°C for 2-6 hours and then naturally cooled to room temperature.
[0016] The obtained cationic Pt single-site catalyst can be used for the dehydrogenation of propane to propylene under harsh reaction conditions.
[0017] In the obtained cationic Pt single-site catalyst, Pt is used as the active component for breaking the CH bond, M is used as an auxiliary agent for breaking the Pt-Pt metal bond, and Ce is used as a doping auxiliary agent for breaking the Pt-M bond. The difference in interaction force between M and Ce species is used to anchor Pt in the single-site cationic state on the carrier SiO 2 The surface of the reactor can achieve efficient dehydrogenation of propane to propylene.
[0018] The beneficial effects of the present invention are: (1) The present invention uses three metal salts and SiO 2 Using MCe as raw material, a cationic Pt single-site catalyst was prepared by equal volume impregnation of multi-metal salts, standing, drying, grinding and calcination, in which the Pt active sites were anchored on the support surface by highly dispersed MCe nano-islands.
[0019] (2) The preparation process of the present invention is simple to operate, the process parameters are easy to control, and the repeatability is good. 2The tri-metal component supported catalyst can effectively expose the number of unit-site Pt cations on the support surface, maximizing the catalytic activity while enhancing the structural stability of the active sites through chemical interactions between the additive and the support. Therefore, it exhibits excellent propane dehydrogenation activity (propane conversion greater than 65%), propylene selectivity greater than 92% and long-term catalytic stability under harsh reaction conditions, showing good application prospects in the field of alkane molecular conversion. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD patterns of the catalysts obtained in Examples 2, 4, 5 and 6 are shown in FIG.
[0021] Figure 2 This is a comparison chart of the activities of the catalysts obtained in Examples 2, 4, 5, 6 and Comparative Example 3 in propane dehydrogenation reaction.
[0022] Figure 3 Atomic resolution transmission electron microscopy images (A, F) and element distribution map (BE) of the catalyst obtained in Example 2.
[0023] Figure 4 The X-ray absorption spectra (A) and data fitting spectra (B, C) of the catalysts obtained in Example 2 and Comparative Example 3 are shown. DETAILED DESCRIPTION
[0024] A cationic Pt single-site catalyst based on SiO 2 As a carrier, a ternary metal component consisting of Pt, Ce and M (M = Fe, Zn, Ga, In) is loaded on its surface; wherein, when the sum of the molar percentages is 100%, the content of Pt in the ternary metal component is 5.6%~49.3%, the content of Ce is 29.2%~84.8%, and the content of M is 8.7%~50.7%.
[0025] The preparation method of the cationic Pt single-site catalyst comprises the following steps: (1) The nitrate precursors of Pt, Ce and M are dissolved in deionized water by ultrasonic treatment at room temperature for 2 to 60 min to prepare a uniformly mixed transparent metal salt precursor aqueous solution with a total metal ion concentration of 0.3 to 1.3 M; (2) Add the metal salt precursor aqueous solution prepared in step (1) to SiO 2 The carrier was sealed and allowed to stand at room temperature for 1-2 hours, then transferred to a static oven and dried at 50-100 °C for 8-24 hours to obtain a white solid sample; the volume of the metal salt precursor aqueous solution used was 0.5-3 times the pore volume of the carrier; (3) The white solid sample obtained in step (2) was carefully ground and placed in a muffle furnace. In static air, the temperature was raised to 400-600 °C at a rate of 2-10 °C / min, maintained for 2-6 h, and then naturally cooled to room temperature to obtain fresh PtM (M = Fe, Zn, Ga, In) Ce / SiO 2 catalyst.
[0026] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0027] SiO used 2 The pore volume of the support is 0.1 cm 3 / g.
[0028] Example 1 Weigh 24.3 mg of tetraammine platinum nitrate, 26.4 mg of indium nitrate hexahydrate, and 22.8 mg of cerium nitrate hexahydrate and dissolve them in 0.6 mL of deionized water. Ultrasonicate at 25 °C for 2 min to prepare a uniformly mixed metal salt precursor solution. Then weigh 3 g of SiO 2 The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar percentage of Pt: 34.9%, In: 35.9%, and Ce: 29.2%. The catalyst was recorded as 0.4Pt0.2In0.2Ce / SiO according to the weight percentage of the metal loaded on the carrier. 2 .
[0029] Example 2 Weigh 9.0 mg of tetraammine platinum nitrate, 9.9 mg of indium nitrate hexahydrate, and 57.4 mg of cerium nitrate hexahydrate and dissolve them in 0.6 mL of deionized water. Ultrasonicate at 25 °C for 2 min to prepare a uniformly mixed metal salt precursor solution. Then weigh 3 g of SiO 2 The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar percentage of Pt: 13%, In: 13.5%, and Ce: 73.5%. The catalyst was recorded as 0.2Pt0.1In0.6Ce / SiO according to the weight percentage of the metal loaded on the carrier. 2 .
[0030] Example 3 Weigh 25.7 mg of tetraammine platinum nitrate, 27.7 mg of indium nitrate hexahydrate, and 280.4 mg of cerium nitrate hexahydrate and dissolve them in 0.6 mL of deionized water. Ultrasonicate at 25 °C for 2 min to prepare a uniformly mixed metal salt precursor solution. Then weigh 2 g of SiO 2 The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar content of Pt: 8.5%, In: 8.7%, and Ce: 82.8%. The catalyst was recorded as 0.6Pt0.4In4.5Ce / SiO according to the weight percentage of the metal loaded on the carrier. 2 .
[0031] Example 4 Weigh 9.0 mg of tetraammine platinum nitrate, 7.2 mg of zinc nitrate hexahydrate, and 57.4 mg of cerium nitrate hexahydrate and dissolve them in 0.6 mL of deionized water. Ultrasonicate at 25 °C for 2 min to prepare a uniformly mixed metal salt precursor solution. Then weigh 3 g of SiO 2 The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar percentage of Pt: 13%, Zn: 13.5%, and Ce: 73.5%. The catalyst was recorded as 0.2Pt0.1Zn0.6Ce / SiO according to the weight percentage of the metal loaded on the carrier. 2 .
[0032] Example 5 Weigh 9.0 mg of tetraammine platinum nitrate, 6.6 mg of hydrated gallium nitrate, and 57.4 mg of hexahydrated cerium nitrate and dissolve them in 0.6 mL of deionized water. Ultrasonicate at 25 °C for 2 min to prepare a uniformly mixed metal salt precursor solution. Then weigh 3 g of SiO 2 The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar percentage of Pt: 13%, Ga: 13.5%, and Ce: 73.5%. The catalyst was recorded as 0.2Pt0.1Ga0.6Ce / SiO according to the weight percentage of the metal loaded on the carrier. 2 .
[0033] Example 6 Weigh 9.0 mg of tetraammine platinum nitrate, 5.9 mg of ferric nitrate hexahydrate, and 57.4 mg of cerium nitrate hexahydrate and dissolve them in 0.6 mL of deionized water. Ultrasonicate at 25 °C for 2 min to prepare a uniformly mixed metal salt precursor solution. Then weigh 3 g of SiO 2 The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar percentage of Pt: 13%, Fe: 13.5%, and Ce: 73.5%. The catalyst was recorded as 0.2Pt0.1Fe0.6Ce / SiO according to the weight percentage of the metal loaded on the carrier. 2 .
[0034] Comparative Example 1 (Single Metal Pt Catalyst) 20 mg of tetraammine platinum nitrate was dissolved in 0.1 mL of deionized water and ultrasonicated at 25 °C for 2 min to prepare a uniformly mixed metal salt precursor solution. 2 The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar content of Pt: 100%. According to the weight percentage of the metal loaded on the carrier, it is recorded as 0.5Pt / SiO 2 .
[0035] Comparative Example 2 (PtCe bimetallic catalyst) Weigh 35.3 mg of tetraammine platinum nitrate and 220.9 mg of cerium nitrate hexahydrate and dissolve them in 0.6 mL of deionized water. Ultrasonicate at 25 °C for 2 min to prepare a uniform metal salt precursor solution. Then weigh 3 g of SiO 2 The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar content of Pt: 15.2% and Ce: 84.8%. The catalyst was recorded as 0.6Pt2.4Ce / SiO according to the weight percentage of the metal loaded on the carrier. 2 .
[0036] Comparative Example 3 (PtIn bimetallic catalyst) Weigh 34.4 mg of tetraammine platinum nitrate and 37.3 mg of indium nitrate hexahydrate and dissolve them in 0.6 mL of deionized water. Ultrasonicate at 25 °C for 2 min to prepare a uniformly mixed metal salt precursor solution. Then weigh 10 g of SiO 2The catalyst was prepared by slowly adding the metal salt precursor solution to the carrier, standing at 25 °C for 2 h, and then transferred to a static oven. After drying at 80 °C for 10 h, the catalyst was ground and calcined at 500 °C for 4 h to obtain a catalyst with a molar content of 49.3% Pt and 50.7% In. The molar content of the catalyst was recorded as 0.2Pt0.1In / SiO according to the weight percentage of the metal loaded on the carrier. 2 .
[0037] Figure 1 The XRD patterns of the catalysts obtained in Examples 2, 4, 5 and 6 are shown in Table 1. Figure 1 It can be seen that no metal diffraction peaks appear in the catalysts obtained in Examples 2 and 4, while only very weak Pt characteristic diffraction peaks appear in the catalysts obtained in Examples 5 and 6, indicating that the active metal is highly dispersed on the catalyst surface, which is crucial to the realization of the excellent performance of Pt-based catalysts.
[0038] The catalysts prepared in Examples 2, 4, 5, 6 and Comparative Example 3 were used for propane dehydrogenation reaction. The application steps were as follows: the catalyst was first granulated into 40-60 mesh particles, then mixed evenly with 40-60 mesh quartz sand at a mass ratio of 1:5 and filled into the middle section of the atmospheric pressure quartz tube reactor; the pre-reduction conditions were: 5% H 2 / Ar gas atmosphere, the reduction temperature was 550 ℃ for 2h; the direct dehydrogenation reaction conditions of propane were: 50% C at 20-100 mL / min 3 H 8 The reaction was carried out in an Ar reaction gas at 500-600 °C for 20 h.
[0039] Figure 2 The activity comparison diagram of the catalysts obtained in Examples 2, 4, 5, 6 and Comparative Example 3 for propane dehydrogenation reaction is shown in the figure. 2 The initial catalytic activity of the bimetallic catalyst is low and is accompanied by rapid deactivation. In contrast, the 0.2Pt0.1In0.6Ce / SiO 2 、0.2Pt0.1Zn0.6Ce / SiO 2 、0.2Pt0.1Ga0.6Ce / SiO 2 and 0.2Pt0.1Fe0.6Ce / SiO 2 The conversion rate of propane, propylene selectivity and stability of the catalyst were significantly improved. The above results fully prove that the introduction of Ce can significantly improve the PtM / SiO 2 Catalytic performance of bimetallic catalysts.
[0040] Figure 3The atomic resolution transmission electron microscope image and element distribution map of the catalyst obtained in Example 2 after the reaction. It can be seen from the figure that several bright spots are surrounded by darker species. Combining the atomic number Z contrast and the corresponding element distribution map, it can be inferred that these central bright spots are several isolated Pt atomic active centers, and the surrounding clusters are MCeO x This result is consistent with the changes observed by XRD, which fully proves that the active center structure of the catalyst obtained in Example 2 is a single-site Pt species. x The "nano-islands" anchor the active single-site Pt species, enabling them to maintain a high degree of structural stability during the reaction, thereby achieving stable catalytic performance.
[0041] Figure 4 The X-ray absorption and extended edge data fitting spectra of the catalysts obtained in Example 2 and Comparative Example 3 after the reaction. As can be seen from the figure, the white line position of the catalyst obtained in Comparative Example 3 indicates that the Pt species mainly exists in the form of zero-valent metallic Pt particles, while the Pt species in the catalyst obtained in Example 2 exists in the form of partially valent Pt δ+ cations exist. 3 -In the extended edge fine structure spectrum and wavelet transform, the Pt species in the catalyst obtained in Example 2 mainly exist in Pt-O bonds without Pt-O-Pt bonds and Pt-Pt, indicating that there is no PtO x The weak Pt-M bond signal that appears is a structure that exists in the bulk phase of the aggregate and does not participate in the surface reaction. Therefore, this characterization indicates that the introduction of Ce species interrupts the Pt-M bond and ultimately forms an isolated single-site Pt cation as an active structure for propane dehydrogenation.
[0042] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A cationic Pt single-site catalyst, characterized in that: The catalyst uses SiO2 as a carrier, and a ternary metal component consisting of Pt, Ce and M is loaded on its surface; wherein M is any one of Fe, Zn, Ga and In, and Pt is in a unit point cation state in the ternary metal component.
2. The cationic Pt single-site catalyst according to claim 1, characterized in that: When the sum of the molar percentages is 100%, in the ternary metal component, the content of Pt is 5.6% to 49.3%, the content of Ce is 29.2% to 84.8%, and the content of M is 8.7% to 50.7%.
3. A method for preparing a cationic Pt single-site catalyst as claimed in claim 1, characterized in that: The steps include: (1) dissolving the nitrate precursors of Pt, Ce and M in deionized water by ultrasonication at room temperature to prepare a uniformly mixed aqueous solution of metal salt precursors; (2) loading the metal salt precursor aqueous solution prepared in step (1) onto a SiO2 carrier by an impregnation method to obtain a white solid sample; (3) The white solid sample obtained in step (2) is carefully ground and then calcined in a muffle furnace to obtain the catalyst.
4. The method for preparing a cationic Pt single-site catalyst according to claim 3, characterized in that: The total metal ion concentration of the metal salt precursor aqueous solution obtained in step (1) is 0.3~1.3M.
5. The method for preparing a cationic Pt single-site catalyst according to claim 3, characterized in that: The volume of the aqueous solution of the metal salt precursor used in step (2) is 0.5 to 3 times the pore volume of the support.
6. The method for preparing a cationic Pt single-site catalyst according to claim 3, characterized in that: Specifically, step (2) includes slowly adding the aqueous solution of the metal salt precursor into the SiO2 carrier, sealing and standing at room temperature for 1 to 2 hours, and then transferring to a static oven and drying at 50 to 100°C for 8 to 24 hours.
7. The method for preparing a cationic Pt single-site catalyst according to claim 3, characterized in that: The calcination in step (3) is carried out in static air at 400-600°C for 2-6 hours and then naturally cooled to room temperature.
8. Use of the cationic Pt single-site catalyst as claimed in claim 1 in the dehydrogenation of propane to produce propylene.
Citation Information
Patent Citations
PtIn-coated MFI catalyst as well as preparation method and application thereof
CN113042098A